2015
DOI: 10.1111/epi.13287
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ interest in genetic testing of their offspring in multiplex epilepsy families

Abstract: Summary Objective To evaluate parents’ interest in genetic testing of their offspring in families containing multiple individuals with epilepsy. Methods 77 parents with affected offspring and 173 parents without affected offspring from families containing multiple individuals with epilepsy completed a questionnaire asking about their interest in genetic testing of their offspring. Interest in testing was ascertained in four scenarios defined by clinical utility and penetrance of the gene in the test (100% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…As reported previously, 20 survey participation rates increased with advancing age, and were higher in women than in men, in college graduates versus nongraduates, and in individuals with epilepsy, compared with biologic relatives without epilepsy or married-in individuals. Individuals who completed the survey averaged 53 years of age (standard error of the mean [SEM] 0.70), and 88% were white, non-Hispanic; 59% were women; and 54% were college graduates.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As reported previously, 20 survey participation rates increased with advancing age, and were higher in women than in men, in college graduates versus nongraduates, and in individuals with epilepsy, compared with biologic relatives without epilepsy or married-in individuals. Individuals who completed the survey averaged 53 years of age (standard error of the mean [SEM] 0.70), and 88% were white, non-Hispanic; 59% were women; and 54% were college graduates.…”
Section: Resultssupporting
confidence: 82%
“…The data are from a survey of families containing multiple individuals with epilepsy who previously participated in genetic research. Our earlier findings from this study show that interest in genetic testing is strong in these families, particularly when it is likely to lead to improved clinical care . We also found that felt stigma was increased in family members with epilepsy who perceived that genetics played a “medium” or “big” role in causing epilepsy in the family …”
mentioning
confidence: 52%
See 1 more Smart Citation
“…15 To investigate the relations of genetic attribution to perceived psychosocial impact of epilepsy, we analyzed data from a study of families with multiple individuals with epilepsy who had previously participated in genetic research. 16,17 Also, felt stigma was higher in people with epilepsy who attributed their disorder to a genetic cause than in others. To date, results indicate that interest in genetic testing for oneself or one's offspring is strong, especially if genetic findings are likely to have clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…To date, results indicate that interest in genetic testing for oneself or one's offspring is strong, especially if genetic findings are likely to have clinical utility. 16,17 Also, felt stigma was higher in people with epilepsy who attributed their disorder to a genetic cause than in others. 18 Additionally, among family members without epilepsy, the perceived chance of having an epilepsy-related mutation was associated with increased prevalence of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%